1988
DOI: 10.1016/0377-8401(88)90127-7
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of tannin-containing and tannin-free faba beans (Vicia faba) by young chicks: Effects of pelleting feeds on energy, protein and starch digestibility

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
1
3

Year Published

1992
1992
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(37 citation statements)
references
References 17 publications
3
30
1
3
Order By: Relevance
“…The results of the N balance experiments confirmed negative effects of FB tannins on protein digestibility as found in other studies (Bourdon and Perez, 1984;Lacassagne, 1988;Jansman, 1989). Besides forming complexes with dietary and enzymatic proteins, tannins cause in rats an increase of secretion of salivary proline-rich protein with a high affinity to tannins (Mehansho et al, 1987;Jansman, 1993).…”
Section: Effect Of Tannins On Growth Performance Of Ratssupporting
confidence: 89%
“…The results of the N balance experiments confirmed negative effects of FB tannins on protein digestibility as found in other studies (Bourdon and Perez, 1984;Lacassagne, 1988;Jansman, 1989). Besides forming complexes with dietary and enzymatic proteins, tannins cause in rats an increase of secretion of salivary proline-rich protein with a high affinity to tannins (Mehansho et al, 1987;Jansman, 1993).…”
Section: Effect Of Tannins On Growth Performance Of Ratssupporting
confidence: 89%
“…However, even the mild heat treatment (90−110 °C) during expander-processing may had a positive effect on FB carbohydrate utilization. Lacassagne et al (1988) have previously reported that heat treatment had a considerable effect on faba bean starch digestibility and energy value.…”
Section: Resultsmentioning
confidence: 99%
“…It should be considered that even if the essential amino acids are higher than NRC requirement, probably they are less available. Several authors (Ortiz et al, 1993, Lacassagne et al, 1988Grosjean et al, 2000) reported that tannins of faba bean reduce energy and protein digestibility in poultry due to formation of tannin-protein complexes. Vilariño et al (2009), comparing faba bean seeds selected for low or high tannins and low or high vicine and convicine contents, confirm that tannins reduced apparent energy and protein digestibility of faba bean in chickens whereas vicine and convicine have a negative effect only on energy.…”
Section: Resultsmentioning
confidence: 99%